THE HUMAN DIMENSION OF POSTINDUSTRIALISM IN THE CONTEXT OF GLOBALIZATION PROCESSES - Атаманчук, Зорина; Макогін, Зоряна; Дідович, Іван (SWorldJournal, 2023)
The article substantiates that the economic progress and international competitiveness of countries mainly depends on the processes of intellectualization of production, that consists of the predominance of intellectual factors of ensuring labor productiv